Esterases para a análise de variabilidade genética em mandacaru (Cactaceae) - Peron, Ana Paula (2011)
Polyacrylamide Gel Electrophoresis was employed in current investigation to evidence α- and β- esterases in order to estimate and compare the genetic variability among mandacaru populations observed in three Brazilian regions: in Maringá PR, south Brazil; in Picos PI, northeastern Brazil; and in the Atlantic Rain Forest, Juréia beach, SP, southeastern Brazil. Mandacuru plants of the three regions have similar stalk morphology although they are considered different species, or rather, Cereus jamacaru (northeastern region), C. peruvianus (southern region) and C. hildmaniannus (southeastern region). The isozymes α- and β- esterases were considered as codominant markers, adequate to analyze the genetic diversity and the manner populations are genetically structured. Consequently, the detection of specific alleles and/or alleles with different frequencies in different populations may be used as parameters to estimate differentiation level in populations. The loci Est-3, Est-2, Est-5 and Est-14 were characterized as diagnostic sites since they may be employed to differentiate mandacaru plants of the northeastern and southern regions. Exclusive alleles were reported in mandacaru plants in Maringá (Est-31) and in Picos (EST-21, Est-23, Est-24, Est-53 e Est-144). The differential frequency of the various alleles in the above mentioned plants determined a significant genetic differentiation (FST = 0.2132) among mandacaru populations. Whereas mandacaru plant populations in Picos had a higher α- and β-esterases diversity, similarity relationships among plants of the three regions showed identity rates varying between 0.5992 (between plants of the southeastern and northeastern regions) and 0.7787 (between plants of the southern and northeastern regions). These factors indicate that mandacaru populations which are representative of the Brazilian southern, southeastern and northeastern regions can be considered as different species of the genus Cereus, namely, C. peruvianus, C. hildmaniannus and C. jamacaru, respectively.